Analisis Penggunaan Bahasa Digital pada Aplikasi Mobile Check-In dalam Pelayanan Hotel di Rooms Inc Hotel Semarang - Mohamad Nur Ilham; Yati Haryati; Ivo Dinasta Yanuar (UIN Mahmud Yunus Batusangkar, 2026)
The development of digital technology in the hospitality industry has prompted a change in the service system from face-to-face communication to digital application-based communication. Rooms Inc Hotel Semarang uses the Just IN Mobile Check-in Mobile application as a service innovation to make the check-in process easier for guests. However, the use of digital language, symbols, and communication features in the application still poses barriers to understanding for some consumers. This study aims to analyze the use of digital language in the Mobile Check-in application in hotel services at Rooms Inc Hotel Semarang. The research focus includes forms of digital communication, understanding consumer semiotics, and the impact of digital language on consumer decisions in using hotel services. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study show that digital communication in the Just IN Mobile application has changed the service pattern from face-to-face communication to a more efficient, fast, and practical digital system. The digital language used is designed to be simple, clear, and easy to understand, making it easier for users to understand instructions and use the application. Digital communication is also supported by the use of icons, colors, notifications, audio, and video guides that strengthen the user's understanding of the application system. From a semiotic perspective, users understand symbols at the denotative, connotative, and mythical levels that shape the perception of hotels as modern, safe, professional, and technology-based. In addition, digital language has a positive impact on consumer decisions through increased convenience, efficiency, security, and service satisfaction. This research shows that the integration of digital communication and human interaction is an important factor in creating effective and quality hotel services